2020
DOI: 10.3892/mmr.2020.11406
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pivotal genes and pathways in the synovial tissue of patients with rheumatoid arthritis and osteoarthritis through integrated bioinformatic analysis

Abstract: rheumatoid arthritis (ra) and osteoarthritis (oa) are the two most common debilitating joint disorders and although both share similar clinical manifestations, the pathogenesis of each is different and remains relatively unclear. The present study aimed to use bioinformatic analysis to identify pivotal genes and pathways involved in the pathogenesis of ra. Microarray datasets from patients with ra and oa were obtained from the Gene expression omnibus (Geo) database and differentially expressed genes (deGs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…PTPN22 gene is widely expressed in myeloid lineages, including B cells, natural killer cells, and neutrophils, acting as the safeguard for both B cell receptors and T cell receptors signaling pathways. 24 In our study, there was a significant higher CTLA-4 relative expression in RA patients versus controls which was consistent with findings of Aihaiti et al, 2020 that demonstrated a significant increase in CTLA-4 expression in RA synovial tissue, 25 but other studies showed minor to a non-detectable level of CTLA-4 membrane expression on the helper or cytotoxic T cells. 15,26 The increased expression of CTLA-4 was reported only at the level of the soluble molecule (sCTLA-4) 12,13,15 or on synovial membranes of RA joints.…”
Section: Discussionsupporting
confidence: 92%
“…PTPN22 gene is widely expressed in myeloid lineages, including B cells, natural killer cells, and neutrophils, acting as the safeguard for both B cell receptors and T cell receptors signaling pathways. 24 In our study, there was a significant higher CTLA-4 relative expression in RA patients versus controls which was consistent with findings of Aihaiti et al, 2020 that demonstrated a significant increase in CTLA-4 expression in RA synovial tissue, 25 but other studies showed minor to a non-detectable level of CTLA-4 membrane expression on the helper or cytotoxic T cells. 15,26 The increased expression of CTLA-4 was reported only at the level of the soluble molecule (sCTLA-4) 12,13,15 or on synovial membranes of RA joints.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, according to the results of network analysis, one of the ELP mechanisms in anti-RA effects may be associated with regulating the PI3K/AKT signaling pathway. Cytokine-cytokine receptor interaction plays a vital role in both innate and adaptive inflammatory host defenses and development and repair processes aimed at the restoration of homeostasis, which is involved in the pathogenesis of inflammatory and autoimmune diseases including RA [ 45 ]. Notably, there are implicated in plenty of studies also suggesting cytokine-cytokine interactions involved in the pathogenesis of RA [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the research is concentrated on one disease at a time [ 54 , 55 ]. Recent advances in the study of RA and PD, OA and PD, RA and OA, as well as RA, OA, and PD separately, have been made by utilizing the data generated from high-throughput technologies (DNA microarrays and RNAseq), and Omics-based techniques [ 5 , 6 , 8 , 16 , 20 , 37 , 39 , 56 , 57 , 58 ]. However, their applicability is limited when it comes to identifying integrated signature molecules for RA, OA, and PD together.…”
Section: Discussionmentioning
confidence: 99%